Does Digital Transformation Improve Business Resilience? The Role of Organizational Adaptation with Innovation, Digitalization, and Marketing Strategies - Juniansyah, M. Andri; Rosyidah, Dania Meida; Pahrijal, Rival; Ardhiyansyah, Andri (Jurnal Maksipreneur, 2025)
This study explores the impact of digital transformation on business resilience among Indonesian Micro, Small, and Medium Enterprises (MSMEs), with organizational adaptation serving as a mediator. Using a quantitative approach and Structural Equation Modeling with Partial Least Squares (SEM-PLS), this research investigates 180 MSME respondents' data. The results show that digital transformation, operational digitalization, product innovation, and digital marketing strategies impact business resilience both directly and indirectly through organizational adaptation. Organizational adaptation, per se, is discovered to be a key contributor to resilience, implying MSMEs' ability to respond effectively, innovate, and reorganize activities when faced with external shocks. The evidence also confirms that adaptive capability mediates digital transformation and business resilience. These findings enhance the theory of dynamic capabilities in the context of digital disruption and provide practical implications for the digital strategies and policy development of MSMEs in emerging economies.